The Rohingya Refugee Crisis: A Political and Humanitarian Aspects - Khadka, Bijaya (NPRC Journal of Multidisciplinary Research, 2025)
Background: The Rohingya, a predominantly Muslim ethnic minority in Myanmar, form the world’s largest stateless population. The roots of the current crisis lie in the 1982 Citizenship Law, which systematically stripped them of citizenship, rendering them stateless and subject to decades of state-sponsored persecution and discrimination. A brutal military crackdown in 2017, described by the UN as a "textbook example of ethnic cleansing," forced over 700,000 Rohingya to flee to Bangladesh, joining hundreds of thousands displaced in earlier waves of violence. Today, the crisis is protracted, with over 1.1 million Rohingya refugees living in camps in Bangladesh, and conditions inside Myanmar’s Rakhine State described as the worst in decades. Objective: This paper aims to analyze the Rohingya refugee crisis through interconnected political and humanitarian lenses. It examines the humanitarian consequences—including mass displacement, human rights abuses, and dire conditions in refugee camps—alongside the political factors, such as the failure of the Responsibility to Protect (R2P) doctrine, geopolitical interests, and the pursuit of accountability through international justice mechanisms. Methods: The analysis employs a qualitative research approach, incorporating a comprehensive review of reports from international organizations (including the UN and human rights groups), policy documents, and statements from recent high-level diplomatic conferences, such as the UN General Assembly’s High-Level Conference on the situation in September 2025. Findings: • Deepening Humanitarian Crisis: Refugee camps in Cox’s Bazar, Bangladesh, face severe overcrowding and resource strain. Humanitarian response remains "chronically underfunded," with the 2025 response plan only 12% funded, leading to cuts in food rations and essential services. Refugees lack access to formal education and legal livelihoods, fueling desperation and risks of radicalization. • Ongoing Persecution and Conflict: Inside Myanmar, the situation for the remaining Rohingya population remains dire. They are caught between junta forces and ethnic armed groups like the Arakan Army, facing aerial attacks, arson, and movement restrictions. A planned election by the military junta is widely seen as a "sham" that will exacerbate violence rather than provide a path to stability. • Political Stalemate and Accountability: Geopolitical interests, particularly the support of China and Russia for the Myanmar junta, have paralyzed the UN Security Council and prevented a robust international intervention under the R2P doctrine . However, accountability efforts are progressing through cases at the International Court of Justice (ICJ) and the International Criminal Court (ICC), which is investigating atrocity crimes. Conclusion: The Rohingya crisis remains a severe and unresolved challenge that tests the international community’s commitment to human rights and protection. A sustainable solution requires immediate, scaled-up humanitarian funding, renewed diplomatic pressure on Myanmar to grant citizenship and full rights to the Rohingya, and unwavering support for international justice mechanisms. Ultimately, safe, voluntary, and dignified repatriation is impossible without a fundamental political change in Myanmar. Implication: The protracted nature of the crisis highlights a critical failure of international governance and the limitations of existing frameworks like R2P when confronted with assertions of national sovereignty. The crisis threatens regional stability and sets a dangerous precedent for impunity for mass atrocities. A shift in policy is urgently needed, moving from short-term humanitarian relief to a long-term strategy that empowers Rohingya refugees and involves them directly in shaping their own future.